ANALISIS TINGKAT KEMAMPUAN LITERASI MEMBACA SISWA KELAS IV DALAM MENYELESAIKAN SOAL ASESMEN KOMPETENSI MINIMUM (AKM) BERBASIS TEKS INFORMASI DI SD SWASTA TIARA - Ibnatun Salis; Dian Armanto; Anita Yus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of the Minimum Competency Assessment (AKM) within the Independent Learning policy aims to transform students' critical reasoning through reading literacy. However, the reality on the ground shows that elementary school students' literacy skills are still classified as moderate, especially in understanding textual information. Based on this problem, this study aims to describe in depth the level of reading literacy skills of fourth-grade students at Tiara Private Elementary School in solving AKM questions based on informational texts and identify specific challenges faced by students. This quantitative descriptive study involved 30 fourth-grade students as the research sample. Data collection was carried out through documentation and a reading literacy test in the form of an essay that has been verified as valid and reliable. The results of the study indicate that student literacy levels vary across cognitive processes. At the information-finding level, 25 students (84%) reached the "Proficient" category, and at the interpretation-integration level, 21 students (70%) reached the "Proficient" category. However, at the evaluation-reflection level, 17 students (57%) remained at the "Basic" level, characterized by weak critical argumentation. The main obstacle identified was students' difficulty synthesizing information between paragraphs and connecting text content with personal experiences. This finding underscores the need for innovative learning strategies to strengthen higher-order cognitive processes in elementary school students.